Increasing Autonomous Learning through Metacognitive Awareness - Sri Kamaliasari (Akademika: Jurnal Keagamaan dan Pendidikan, 2023)
Metacognition awareness has contributed significantly to fostering students’ autonomous learning. This article gives information about how metacognition awareness helps students monitor their own learning progress and take control of the learning in order to improve their learning performance. Reviewing research on metacognition awareness has several benefits. First, researchers who are interested in investigating metacognition awareness in language learning gain access to previews research findings which provides insights to conduct future research on metacognition awareness from different perspectives and theories. Secondly, language teachers can gain a clear understanding of metacognition awareness and metacognitive strategies for providing it to their learners alongside the results and conclusions from the previous studies. Finally, it is a ready-made reviews for those who are lack of the available studies on metacognition so that they have access to refer to the previous studies once they conduct further research on metacognition in foreign/second language learning.